(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Little information is currently available on the potential environmental risks that fungicides applied during wheat cultivation and remaining in straw may have for mushroom production. The substrate for many cultivated mushrooms is mostly based on cereal straw. This review aimed to answer the question whether residues of the fungicides commonly used in wheat production and remaining in straw could be directly or indirectly responsible for changes in yields of Agaricus bisporus. Potential chemical risks of eight fungicides (for wheat treatments) for A. bisporus: mancozeb, carbendazim, thiophanate-methyl, carbendazim+cyproconazole, carbedazim+flusilasole, captan, chlorothalonil and trifloxystrobin are disscused. Only the value of maximum residue level of flusilasole and its formulation was evaluated as higher than medium effective concentration of the fungicide for A. bisporus. As a conclusion, flusilazole treatment could be a limiting factor for using straw for composting and mushroom cultivation.